A Fractal Approach for Predicting Unsaturated Hydraulic Conductivity of Deformable Clay. (2nd May 2019) - Tao, Gaoliang; Zhu, Xueliang; Cai, Jianchao; Xiao, Henglin; Chen, Qingsheng; Chen, Yin
Abstract : The relative hydraulic conductivity is one of the key parameters for unsaturated soils in numerous fields of geotechnical engineering. The quantitative description of its variation law is of significant theoretical and technical values. Parameters in a classical hydraulic conductivity model are generally complex; it is difficult to apply these parameters to predict and estimate the relative hydraulic conductivity under deformation condition. Based on the fractal theory, a simple method is presented in this study for predicting the relative hydraulic conductivity under deformation condition. From the experimental soil-water characteristic curve at a reference state, the fractal dimension and air-entry value are determined at a reference state. By using the prediction model of air-entry value, the air-entry values at the deformed state are then determined. With the two parameters determined, the relative hydraulic conductivity at the deformed state is predicted using the fractal model of relative hydraulic conductivity. The unsaturated hydraulic conductivity of deformable Hunan clay is measured by the instantaneous profile method. Values of relative hydraulic conductivity predicted by the fractal model are compared with those obtained from experimental measurements, which proves the rationality of the proposed prediction method.